Islam and civilisational renewal: the case for "sacred science" - Moten, Abdul Rashid (International Institute of Advanced Studies (IAIS) Malaysia and Pluto Press (London), 2013)
The Islamic or Muslim civilisation was once at an incomparable peak in terms of all possible indicators of development. But a destruction of the spirit of inquiry and original research so distinctly associated with civilisational development served to sow the seeds of decay and render it easy prey for colonial exploitation. Confronted with a world dominated by Western science and technology, Muslim scholars have been searching for ways to regain their freedom, control their collective lives and link their past to the future. Some opted for a “secularisation thesis”, others advocated liberalisation, still others advocated adoption of science since the Qur’an and science could be seen to complement each other. Seyyed Hossein Nasr asks for the revival of Islamic science. Through a textual analysis of his writings, this study shows that Nasr provides a critique of the Western science and technology, while urging Muslims to study it in depth in order to undertake an authentic critique and to develop a new paradigm to usher in the new golden days of Islam.